1984
DOI: 10.1111/j.1365-2141.1984.tb06112.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of chromosome abnormalities in chronic lymphocytic leukaemia

Abstract: Lymphocytes from 33 out of 63 patients with B-cell chronic lymphocytic leukaemia (B-CLL) were successfully stimulated for cytogenetic analysis by means of two B-cell mitogens: pokeweed mitogen and lipopolysaccharide-B, used after pretreatment of the cells with neuraminidase and galactose oxidase. All patients had abnormal clones in 30-100% of the cells analysed. Chromosomes more frequently involved were Nos. 1, 3, 6, 11, 12, 13 and 14. The most common abnormality was a marker 14q+ (breakpoint 14q32) seen in 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
4
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(64 citation statements)
references
References 23 publications
6
53
4
1
Order By: Relevance
“…Furthermore, it has been found that CLL patients with a translocation involving 14q32 have poorer prognosis. 7,35,36 This subgroup had the same poor prognosis as other patients with translocations in our analysis.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, it has been found that CLL patients with a translocation involving 14q32 have poorer prognosis. 7,35,36 This subgroup had the same poor prognosis as other patients with translocations in our analysis.…”
Section: Discussionsupporting
confidence: 71%
“…Deletion of 11q in CLL has been previously reported with a varying frequency. Hernandez et al [27] found deletion of 11q in 12% of patients, Pittman and Catovsky [21] in 9% and Juliusson and Gahrton [9] in 6% of available patients. These differences are the results of using CC with G-banding by which some deletions had been missed.…”
Section: Discussionmentioning
confidence: 99%
“…In B-cell chronic lymphocytic leukemia (CLL), a gain of chromosome 12 and translocations involving 14q32 are the most frequent chromosomal aberrations (5,6). The presence of karyotypic abnormalities is associated with a poor prognosis.…”
mentioning
confidence: 99%